Institutional change through interstitial emergence: the Growth of Alternative Dispute Resolution in U.S. Law, 1970-2000 - Morrill, Calvin (Revista de Estudos Empíricos em Direito, 2017)
How can be explained the dramatic changes in the growth of informal dispute resolution as “alternatives” to adjudication between 1970-2000? This article gives an answer to this question by using the historical case of U.S. Alternative Dispute Resolution (ADR) in the last third of the 20th century to ground empirically a theory of interstitial emergence. By focusing on interstitial emergence, the article demonstrates how informal interaction across multiple organizational fields can provide cultural accounts for new formal structures. The analysis furthers the integration between institutional analysis in organizational and legal sociology, but does so by borrowing conceptual leads from social movement theory to elaborate and develop a framework for understanding institutional innovation and change. In doing so, it draws specific attention to issues of agency and emergent signification. The remainder of the article contains sections that narratively illustrate interstitial emergence and its dimensions using evidence from the U.S. ADR case. The conclusion extends the argument beyond ADR to consider alternative developments in the U.S. medical field and implications for institutional analysis, more generally.